Effect of grazing management of tropical pasture utilization - Tergas, Luis Eduardo (International Center for Tropical Agriculture, 1993)
The factors of grazing management that influence tropical pasture utilization are discussed in this review. The principal objective is to consider stocking rate and grazing system effects-and their interaction-as related to the evaluation of germplasm under grazing. It is inferred that the study of interactions between stocking rate and grazing system is important for determining, not only animal production, but also management of forage species (principally legumes associated with grasses) and so ensure their persistence. It is therefore suggested that, when evaluating new germplasm in small plots, management factors be included in order to better understand the alternatives for use of the germplasm within a determined ecosystem or, in simpler grazing tests, the potential that the new germplasm will have for animal production.